The role of metformin in treatment of weight gain associated with atypical antipsychotic treatment in children and adolescents: A systematic review and meta-analysis of randomized controlled trials - Mansuri, Zeeshan; Makani, Ramkrishna; Trivedi, Chintan; Adnan, Mahwish; Vadukapuram, Ramu; Rafael, John; Lodhi, Ashutosh; Reddy, Abhishek (Frontiers in Psychiatry, 2022)
Introduction: Second-generation antipsychotics are associated with significant weight gain. The meta-analysis was performed for published randomized studies of Metformin for the treatment of weight gain in children and young adults treated with second-generation antipsychotics. Methods: Search was performed for the randomized studies which evaluated the effect of Metformin on the treatment of weight gain in children and adolescents undergoing treatment with second-generation antipsychotics. From all the studies, data were collected for change in anthropometric-biochemical parameters, drug discontinuation rate, and side effects among the groups. The random-effects method was used for meta-analysis. Results: Four studies with were included in the final analysis (213 patients; metformin:106; control:107). After pooled analysis, 12-16 weeks of metformin therapy was associated with a significant reduction in weight (mean difference (MD): -4.53 lbs, p-value <0.001), and BMI z score [MD, -0.09, p-value:0.004] compared to control. Metformin was also associated with a significant reduction in insulin resistance [MD: -1.38, p-value:0.002]. There were higher odds of nausea-vomiting [OR: 4.07, p-value: 0.02] and diarrhea [OR: 2.93, p-value: 0.002] in the metformin group. However, there was no difference in drug discontinuation rate [OR: 1.45, p-value: 0.56]. Conclusions: Metformin may prove beneficial in the treatment of weight gain in children treated with second-generation antipsychotics. The pooled treatment effect showed a significant reduction in BMI Z-score and weight in just 12-16 weeks. The limitations include small sample size, variation in metformin dose, and duration of treatment. This meta-analysis should be interpreted as promising, and further larger studies are warranted before drawing a conclusion.